Concordant association validates MGMT methylation and protein expression as favorable prognostic factors in glioma patients on alkylating chemotherapy (Temozolomide) - Arshad A. Pandith (Nature Portfolio, 2018)
Abstract O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation and its subsequent loss of protein expression has been identified to have a variable impact on clinical outcome of glioma patients indicated for chemotherapy with alkylating agents (Temozolomide). This study investigated methylation status of MGMT gene along with in situ protein expression in malignant glioma patients of different histological types to evaluate the associated clinical outcome vis-a-vis use of alkylating drugs and radiotherapy. Sixty three cases of glioma were evaluated for MGMT promoter methylation by methylation-specific PCR (MS-PCR) and protein expression by immunostaining (IHC). Methylation status of MGMT and loss of protein expression showed a very high concordant association with better survival and progression free survival (PFS) (p < 0.0001). Multivariate Cox regression analysis showed both MGMT methylation and loss of protein as significant independent prognostic factors in glioma patients with respect to lower Hazard Ratio (HR) for better OS and PFS) [p < 0.05]. Interestingly concordant MGMT methylation and lack of protein showed better response in TMZ therapy treated patient subgroups with HR of 2.02 and 0.76 (p < 0.05). We found the merits of prognostication of MGMT parameters, methylation as well as loss of its protein as predictive factors for favorable outcome in terms of better survival for TMZ therapy.